Magnitude and predictors of normal-weight central obesity- the AWI-Gen study findings - Shukri F. Mohamed; Tilahun Nigatu Haregu; Christopher Khayeka-Wandabwa; Stella Kagwiria Muthuri; Catherine Kyobutungi (Taylor & Francis Group, 2019)
Background: Normal-weight central obesity is associated with higher mortality than general obesity as defined by body mass index, particularly in the absence of central fat distribution. Objective: The aim of this study was to examine the magnitude and predictors of normal-weight central obesity in an urban informal settlement setting in Kenya. Methods: We used data from the AWI-Gen study, a cross-sectional survey targeting randomly selected consenting adults between the ages of 40-60 in two urban informal settlements of Nairobi between 2014 and 2016. Central obesity was determined using waist circumference, waist to hip ratio, visceral fat thickness, and subcutaneous fat thickness. General obesity was determined using body mass index (BMI). Results: About 20.0% of participants in the study had general obesity. The prevalence of central obesity as measured by waist circumference was 52.0%, by waist-to-hip ratio was 53.5%, by visceral fat thickness was 32.4% and by subcutaneous fat thickness was 49.2%. The prevalence of normal-weight central obesity in the study population was highest when measured by waist to hip ratio (38.1%) and lowest when measured by visceral fat thickness (18.1%). Factors associated with normal-weight central obesity as assesses by waist circumference were being female, of older age, and in full-time employment. Older age was associated with normal-weight central obesity as assessed by waist to hip ratio. Conclusion: The findings highlight a significant prevalence of normal-weight central obesity among adults in a poor urban setting in Kenya, pointing to women as a key target group for focused interventions. Longitudinal studies are needed to establish whether there is a link between normal-weight central obesity and mortality in such settings as has been found in other settings.